Prevalência de infecção oculta pelo vírus da hepatite B em doadores de sangue do noroeste do estado do Paraná, Brasil - Vizoni, Silvana Lorenzi (2015)
The occult hepatitis B now constitutes the greatest risk of infection post-transfusion hepatitis B virus in several countries and is comparatively higher than the risk for hepatitis C virus or human immunodeficiency virus. The presence of HBV DNA in a high percentage of anti-HBc samples isolated highlights the importance of a rigorous screening process o prevent hepatitis B occult. The objective of this study was to evaluate the prevalence of occult hepatitis B in blood donors of northwestern Paraná state. Samples were collected from 236 donors of the northwestern Paraná state blood. The samples were divided into two groups: Group I (n = 118) with all negative serological markers and Group II (n = 118) with anti-HBc positive. The search of serological markers HBsAg, anti-HBc and anti-HBs to HBV was performed by immunoassay with microparticles chemiluminescence (CMIA) and quantification of HBV viral load by real time polymerase chain reaction with sensitivity <10 IU / mL. The sociodemographic profile between groups I and II showed that there were significant differences with regard to gender, marital status and education level. In group II was predominantly female, married individuals, and less educated. The anti-HBs was present in most samples of group II (anti-HBc positive). The anti-HBc alone was found in 11.8%. All samples showed undetectable viral load. These results are similar to other studies conducted in Brazil with diverse populations. The absence of detectable HBV DNA in the population can be explained by the population studied by rigorous clinical screening procedures, the prevalence of HBV in the region and sample used. No cases were detected OBI in blood donors of northwestern Paraná state region.